Pesantren Governance in Countering Radicalism and Islamophobia: The Case Study of Darussalam Martapura - Zaidan Almas; Khairil Anwar; Mowafg Abrahem Masuwd (UIN Raden Mas Said Surakarta, 2026)
This study examines how Darussalam Islamic Boarding School Martapura manages institutional practices to address radicalism, extremism, and Islamophobia. Using a qualitative case study, data were collected through observations, semi-structured interviews, and document analysis involving leaders, teachers, students, alumni, and community figures. The analysis reveals that the pesantren’s response is not limited to value transmission but is embedded in a systematic management pattern that regulates curriculum design, moral authority, students’ information ecology, and public communication. The study identifies a protective–participatory management model operating through four interconnected pillars: (1) a deliberately moderated ideological curriculum, (2) the kyai’s moral authority as a daily mechanism of value control, (3) institutional regulation of students’ digital and informational exposure, and (4) proactive public engagement to counter Islamophobic stigma. This model demonstrates that the pesantren’s resilience against radicalism and Islamophobia lies not merely in its doctrinal commitment to moderation, but in how moderation is managerially engineered through institutional control and community participation. The study contributes analytically by reframing pesantren from sites of value education into organizational systems of ideological governance that actively filter, supervise, and communicate religious moderation in the digital era.